PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Pada Sektor Agrikultur yang Terdaftar di Bursa Efek Indonesia Periode 2016-2018) - Kinanti Chandra Sari; Devi Farah Azizah (Jurnal Administrasi Bisnis, 2019)
Social responsibility or commonly known as Corporate Social Responsibility (CSR) is now indeed an issue that is being hotly discussed amid the rampant negative environmental impacts caused by the operation of a company. The purpose of this study was to determine the effect of Corporate Social Responsibility (CSR) variable to Company's Financial Performance which is proxied by Return On Assets (ROA), Return On Equity (ROE) and Earning Per Share (EPS) in agricultural sector companies listed in IDX 2016 – 2018 period. The type of research used is explanatory research. The object of this research is the agricultural sector companies listed on the Indonesia Stock Exchange for the 2016 – 2018 period. The number of objects in this study were 16 companies with 3 years of research duration. The data analysis technique used is descriptive statistics and hypothesis testing. The results of this study indicate that the Corporate Social Responsibility (CSR) variable affects the Company's Financial Performance which is proxied by Return On Assets (ROA), Return On Equity (ROE) and Earning Per Share (EPS). Keywords: Corporate Social Responsibility (CSR), Return On Assets (ROA), Return On Equity (ROE), Earning Per Share (EPS). АBSTRАK Tanggung jawab sosial atau biasa dikenal dengan istilah Corporate Social Responsibility (CSR) kini memang menjadi isu yang sedang hangat diperbincangkan ditengah maraknya dampak negatif  lingkungan yang diakibatkan beroperasinya suatu perusahaan. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh variabel Corporate Social Responsibility (CSR) terhadap Kinerja Keuangan Perusahaan yang di proksikan dengan Return On Assets (ROA), Return On Equity (ROE) dan Earning Per Share (EPS) pada perusahaan sektor agrikultur yang terdaftar di BEI periode 2016 - 2018. Jenis penelitian yang digunakan adalah explanatory research. Objek penelitian ini adalah perusahaan sektor agrikultur yang terdaftar di Bursa Efek Indonesia periode 2016 - 2018. Jumlah objek dalam penelitian ini adalah 16 perusahaan dengan lama penelitian 3 tahun. Teknik analisis data yang digunakan yaitu statistik deskriptif dan pengujian hipotesis. Hasil dari penelitian ini menunjukkan bahwa variabel Corporate Social Responsibility (CSR) berpengaruh terhadap Kinerja Keuangan Perusahaan yang di proksikan dengan Return On Assets (ROA), Return On Equity (ROE) dan Earning Per Share (EPS). Kata Kunci: Corporate Social Responsibility (CSR), Return On Assets (ROA), Return On Equity (ROE), Earning Per Share (EPS).